Sosialisasi Dan Edukasi Media Kahoot Sebagai Media Pembelajaran Interaktif Siswa Pada SMP N 1 Konawe - Mclean HY; Ramli Ramli; Sukmawati Sukmawati; Iin Wahyudi; M.Fadli (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of Community Service activities is to provide outreach and education about the use of the Kahoot application at SMP N 1 Konawe. The participants in this activity were 12 teachers. From the results of the activity, it can be concluded that by conducting training on the use of digital game-based learning media using the Kahoot platform, educators or teachers can provide skills in learning innovation, resulting in enthusiastic and interactive learning in the classroom. So that it can optimize and facilitate the process of evaluating or assessing student learning. Based on the feedback, information was obtained that this activity was very relevant to the needs of PKM participants. Kahoot is effective as a learning medium in supporting classroom learning